2019
DOI: 10.1002/gcc.22714
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear compartmentalization, dynamics, and function of regulatory DNA sequences

Abstract: Transcription regulatory elements (TREs) have been extensively studied on the biochemical level with respect to their interactions with transcription factors (TFs), other DNA segments, and larger protein complexes. In this review, we describe concepts and preliminary experimental evidence for positional changes of TREs within a dynamic, functional nuclear architecture. We suggest a multilayered shell‐like chromatin organization of chromatin domain clusters with increasing chromatin compaction levels from the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 119 publications
1
28
0
Order By: Relevance
“…Fluorescent in situ hybridizations (FISHs) on preserved 3D nuclei have enabled a clear understanding of where chromosomes are located in the 3D nuclear space. Seminal work over the years has shown that chromosomes are arranged in a nonrandom and probabilistic manner in the nuclear space of normal cells (Figure ) and that this organization is maintained during evolution . The functional relevance of this ordered structure was elucidated by Solovei et al in a pivotal study on retinas of diurnal and nocturnal animals: in nocturnal animals, the so‐called “inverted” nuclear chromosomal organization is suited to bundle the light—similar to a prism—and enables enhanced vision in dim light conditions.…”
Section: The 3d Nucleus In Cancer Cells: Where We Are Today and Wherementioning
confidence: 99%
See 2 more Smart Citations
“…Fluorescent in situ hybridizations (FISHs) on preserved 3D nuclei have enabled a clear understanding of where chromosomes are located in the 3D nuclear space. Seminal work over the years has shown that chromosomes are arranged in a nonrandom and probabilistic manner in the nuclear space of normal cells (Figure ) and that this organization is maintained during evolution . The functional relevance of this ordered structure was elucidated by Solovei et al in a pivotal study on retinas of diurnal and nocturnal animals: in nocturnal animals, the so‐called “inverted” nuclear chromosomal organization is suited to bundle the light—similar to a prism—and enables enhanced vision in dim light conditions.…”
Section: The 3d Nucleus In Cancer Cells: Where We Are Today and Wherementioning
confidence: 99%
“…The lecture of Boveri's publications is fascinating and is highly recommended to anyone interested in cell biology, genetics, and cancer. in the nuclear space of normal cells [12][13][14] (Figure 3) and that this organization is maintained during evolution. 15 The functional relevance of this ordered structure was elucidated by Solovei et al 16 in a pivotal study on retinas of diurnal and nocturnal animals: in nocturnal animals, the so-called "inverted" nuclear chromosomal organization is suited to bundle the light-similar to a prism-and enables enhanced vision in dim light conditions.…”
Section: First Observations and Curcial Studies Into The 3d Genome mentioning
confidence: 99%
See 1 more Smart Citation
“…In the human genome, genes fluctuate between various transcriptional states: active, inactive or poised (1)(2)(3). The transcriptional status of each gene is dependent on it's local chromatin architecture and nucleosomal positioning inside the nucleus.…”
Section: Introductionmentioning
confidence: 99%
“…Cremer and Cremer focus on the concepts and preliminary experimental evidence for positional changes of transcription regulatory elements within a dynamic, functional nuclear architecture. They propose a multilayered shell‐like chromatin organization of domain clusters where compaction levels are associated with transcriptional accessibility.…”
mentioning
confidence: 99%